Chinese borrowing patterns in Lao Language: https://doi.org/10.69692/SUJMRD090155 - NIMNUAN, Laion; LEI, WANG (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This article is a study of Chinese borrowing patterns in Lao language as a qualitative study by collecting data and then analyzing, explaining and giving examples with the aim of analyzing Chinese borrowing patterns in Lao language. The results of the study can be summarized as follows: There are two ways to Chinese borrowing patterns in Lao Language: Simplified Chinese borrowing in Lao and Indirect borrowing Chinese words in Lao. Simplified Chinese borrowing in Lao were seen in words with one syllable, two-syllable words, and three-syllable words. Indirect borrowing Chinese words in Lao were seen in words with one syllable, two-syllable words.